Desorption of copper ion from coco peat - Esparagoza, Joanna O.; Reyes, Christy Eunice G.; Candelaria, Ma. Doreen; Tanchuling, Maria Antonia N.; Rivera, Alexis Bryan G.; Samaniego, Jesse O. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Mining is a growing industry that has been a main contributor in the economic development of the Philippines. However, its growth also implies the increase in the amount of mining wastewater produced. Due to the lack of resources to treat their wastewater, small-scale miners directly discharge it to the bodies of water nearby. Coco peat is a cheap agricultural waste that provides an economical solution to the wastewater treatment of small-scale miners by being an effective sorbent material that filters out heavy metals. However, after the process, the spent coco peat has become a hazardous waste and needs to be properly disposed. This study is about the removal of copper (a representative of the heavy metals) from the coco peat using the process of desorption - one of the possible disposal methods for coco peat. This was achieved through elution or mixing the coco peat with an acid desorbing agent. Parameters such as the concentration of the eluent, solid liquid ratio of the coco peat and the eluent, and contact time affect the desorption efficiency, and thus, were varied to detennine the optimum conditions at which maximum amount of copper is desorbed and also to study the kinetics of desorption. The photometer was used to test the desorbed concentration of copper. Among the varying concentrations ranging from O.OOOO1M - 1M, results showed that the highest concentration, with the lowest pH value of 0.00, produced maximum desorption of copper of more than 100%. Most values obtained from the experiments were more than 100% due to the uncertainties brought by mass balance, effect of moisture content and initial copper content. It can be concluded that the stronger the acid, the more copper can be desorbed. However, no trend can be seen on the results of varying solid liquid ratio with the parameter having a negligible effect on the process. Results of varying contact time, which used a solid liquid ratio of 10 and 1M concentration for the acid eluent, show that as short as 10 seconds, the percent desorbed of copper was already nearing 100 percent. The desorption process was fast which makes it easy and efficient in tenns of labor, time and resources. The study of the kinetics of desorption or to determine the rate constant of desorption, the data was fitted to the pseudo-first order model and to the pseudo-second order model. The data fitted well with the pseudo-second order obtaining a measure of goodness, R^2, equal to 1. The rate constant of desorption was calculated to 2.2933 g/mg-min. This indicates the successful reversal of the chemisorption mechanism of the sorption process via another set of chemical procedure called elution.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Coir; Copper; Desorption